M. Therese Lysaught and Michael McCarthy, ed., Catholic Bioethics & Social Justice: The Praxis of US Health Care in a Globalized World, Collegeville, MN: Liturgical Press Academic, 2018. - Slusarski, Shaun (Asian Horizons, 2020)
Therese Lysaught and Michael McCarthy, ed., Catholic Bioethics & Social Justice: The Praxis of US Health Care in a Globalized World, Collegeville, MN: Liturgical Press Academic, 2018. Pp xviii + 439. ISBN: 978-0-8146-8455-9